Ideas on the European stone fruit yellows – as an entomologist can see them - Bozsik, András (Acta Agraria Debreceniensis, 2014)
The European stone fruit yellows (ESFY) is an important endemic disease in Europe which causes in both, the Mediterranean countries and Central Europe serious damage. Its pathogen is the ‘Candidatus Phytoplasma prunorum’. The treatment and healing of the diseased trees and plantations with chemicals do not promise success. Thus, prevention may be the only solution. The transmission and spread of the pathogen happen by infected propagation material (grafting) or a vector (the psyllid, Cacopsylla pruni). Mechanism of the pathogen’s transmission and population dynamics of the vector have been extensively investigated in several European countries, which may allow by the control of C. pruni even to hold back the disease. Diseased stone fruit trees and wild Prunus spp. as main host species play an important role in maintaining and spreading the pathogen. C. pruni collects the pathogen by feeding on these plants and it carries persistently ‘Ca. P prunorum’. Researchers in Hungary have been characterized the disease only in terms of plant pathology, but neither the significance of the vector nor the role of wild Prunus spp. have been studied. This summary intends to give clues to these researches, that not only axe and saw should be the instruments of national control, but knowing the role and population dynamics of the vector the stone fruit production should be more successful.